THE STUDENTS' PERCEPTIONS ON THE CHALLENGES AND STRATEGIES IN STUDYING MATHEMATICS AND SCIENCE USING ENGLISH AT THE INTERNATIONAL CLASS PROGRAM (ICP) OF MATHEMATICS AND SCIENCE FACULTY OF UNM - Sultan Baa; Mansyur Mansyur; Nurul Maghfirah (Fakultas Keguruan dan Ilmu Pendidikan, 2025)
The objectives of the study were to find out the students’ perceptions on: (1) the challenges of studying of learning Mathematics and Science using English as medium of instruction (EMI) at the International Class Program (ICP) of Mathematics Department of the State University of Makassar (UNM); (2) their strategies in learning English at the ICP program. The study applied qualitative research design. Semi structure interview was used to collect data. The participants were the students from Mathematics, Physics, and Chemistry Department who are studying at International Class Program of Mathematics and Science Faculty in 2025 academic year. The data were analyzed using Miles and Huberman’s qualitative data analysis. The study discovered that students who are studying at ICP experienced several challenges, namely language related which consisted of lack of general vocabulary, lack of technical vocabulary, reading comprehension problem, and listening comprehension problem and content related challenges. To overcome these, students employed a variety of strategies such as utilizing dictionary, taking notes, peer/group learning, and utilizing technology. Detailed findings will be presented and their implications discussed